Penerapan Etika Pemasaran Bisnis Syariah Dalam Melaksanakan Bisnis Online Shop - Cinta Auly Salzabilla Suherlan; Nymas Mu’nisah Anggraeni; Alfariedza Vania Zhafira; Popon Sri Susilawati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Indonesia is a country where the majority of the people are Muslims. As the country with largest economy in Southeast Asia and also one of the emerging market economies in the world, businessman should balance it with knowledge of marketing ethics in order to usher in newer and better economic era. These days increasingly fierce business competition and lack of knowledge about marketing ethics can be a deviation in the conduct of the business. In this current era what community wants and needs continue to increase, making businessman carry out all marketing strategies that often violate established marketing norms and ethics. Doing online business can bring many advantages and conveniences for the community, but if these conveniences and advantages are not accompanied by a firm attitude and law, there will be deception, tyranny and cheating each other. Therefore in Islam there is a goal to protect mankind from all injustice. Because when we enter the world of online business, there are many challenges, not just about getting profits but also about maintaining how to do business by always sticking to the principles of Islamic law. Keywords: Marketing, Business, Economy